Development of melanoma clinical quality indicators for the Australian melanoma clinical outcomes registry (MelCOR): A modified Delphi study. (29th April 2022) - Jobson, Dale; Roffey, Benjamin; Arnold, Christopher; Azzi, Anthony; Button‐Sloan, Alison; Dawson, Tamara; Fernandez‐Penas, Pablo; Fishburn, Paul; Gyorki, David E.; Hiscutt, Emma L.; Jakrot, Valerie; Lilleyman, Alister; et al.
Abstract: Background: Clinical quality registries aim to identify significant variations in care and provide anonymised feedback to institutions to improve patient outcomes. Thirty‐six Australian organisations with an interest in melanoma, raised funds through three consecutive Melanoma Marches, organised by Melanoma Institute Australia, to create a national Melanoma Clinical Outcomes Registry (MelCOR). This study aimed to formally develop valid clinical quality indicators for the diagnosis and early management of cutaneous melanoma as an important step in creating the registry. Methods: Potential clinical quality indicators were identified by examining the literature, including Australian and international melanoma guidelines, and by consulting with key melanoma and registry opinion leaders. A modified two‐round Delphi survey method was used, with participants invited from relevant health professions routinely managing melanoma as well as relevant consumer organisations. Results: Nineteen participants completed at least one round of the Delphi process. 12 of 13 proposed clinical quality indictors met the validity criteria. The clinical quality indicators included acceptable biopsy method, appropriate excision margins, standardised pathology reporting, indications for sentinel lymph node biopsy, and involvement of multidisciplinary care and referrals. Conclusion: This study provides a multi‐stakeholder consensus for important clinical quality indicators that define optimal practice that will now be used in the Australian Melanoma Clinical Outcomes Registry (MelCOR).